What Martian Meteorites Reveal About the Interior and Surface of Mars. Issue 12 (18th December 2020) - Udry, A.; Howarth, G. H.; Herd, C. D. K.; Day, J. M. D.; Lapen, T. J.; Filiberto, J.
Abstract: Martian meteorites are the only direct samples from Mars, thus far. Currently, there are a total of 262 individual samples originating from at least 11 ejection events. Geochemical analyses, through techniques that are also used on terrestrial rocks, provide fundamental insights into the bulk composition, differentiation and evolution, mantle heterogeneity, and role of secondary processes, such as aqueous alteration and shock, on Mars. Martian meteorites display a wide range in mineralogy and chemistry, but are predominantly basaltic in composition. Over the past 6 years, the number of martian meteorites recovered has almost doubled allowing for studies that evaluate these meteorites as suites of igneous rocks. However, the martian meteorites represent a biased sampling of the surface of Mars with unknown ejection locations. The geology of Mars cannot be unraveled solely by analyzing these meteorites. Rocks analyzed by rovers on the surface of Mars are of distinct composition to the meteorites, highlighting the importance of Mars missions, especially sample return. The Mars 2020 Perseverance rover will collect and cache—for eventual return to Earth—over 30 diverse surface samples from Jezero crater. These returned samples will allow for Earth‐based state‐of‐the‐art analyses on diverse martian rocks with known field context. The complementary study of returned samples and meteorites will help to constrain the evolution of the martian interior and surface. Here, we review recent findings and advances in the study of martian meteorites and examine how returned samples would complement and enhance our knowledge of Mars. Plain Language Summary: Scientists learn about the formation and evolution of planets, such as Mars, by studying rock samples. Obtaining rock samples from Mars makes it possible to study them in state‐of‐the‐art laboratories on Earth with high degrees of precision and accuracy. Currently, samples from Mars are obtained as meteorites that have been ejected from the planet. We can study these rocks to learn about volcanic processes and their chemistry and timing in the context of martian geology. This review paper summarizes the information we have learned about Mars's geology by analyzing martian meteorites. Most of the data collected provide evidence that the interior of Mars is compositionally varied with high diversity in chemical makeup throughout time. However, most meteorites are relatively young with few older rocks (older than 2.4 billion years old) analyzed to date. The Mars 2020 mission plans on collecting older samples directly from Mars's surface, in the Jezero crater, for eventual return to Earth, as early as 2031. The study of both meteorites and returned samples is essential to gain a full understanding of the interior composition, evolution, and geological characteristics of different locations on the Red Planet. Key Points: Martian meteorites are currently the only samples that we possess from the Red Planet Martian meteorites reveal the compositional diversity of the interior of Mars Returned samples from Mars would allow us to better constrain the compositions of the martian interior and its evolution through time